A CNT-BDD electrode with high adsorption performance and preparation method thereof
By combining carbon nanotubes with boron-doped diamonds to make CNT-BDD electrodes, the problem of low adsorption performance of boron-doped diamond film electrodes is solved, the ozone yield is significantly improved, and other excellent performances of the electrodes are maintained.
Patent Information
- Application Number
- CN202211510269.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The adsorption performance of boron-doped diamond film electrodes is low, which affects their adsorption ability to oxygen-containing substances in the ozone generator, resulting in a decrease in ozone yield.
By combining carbon nanotubes with boron-doped diamonds, CNT-BDD electrodes are made, making them both with boron-doped diamond film electrodes and carbon nanotubes, and their adsorption performance is improved.
The CNT-BDD electrode significantly improves ozone yield, solves the problem of low adsorption performance of boron-doped diamond electrodes, and maintains excellent chemical stability, corrosion resistance and electrical conductivity.
Smart Images

Figure BDA0003970532130000261 
Figure BDA0003970532130000271
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental electrochemistry, and in particular to a CNT-BDD electrode with high adsorption performance and a preparation method thereof. Background Art
[0002] With the progress of social civilization, people's environmental awareness continues to increase, and the control of water pollution has received more and more attention. Ozone has a very strong oxidizing ability. Due to its high efficiency and green characteristics, it has been widely used in water disinfection. Ozone is extremely unstable, so ozone cannot be stored and transported in bottles and cans. It can only be made and used on the spot. Therefore, how to prepare ozone more efficiently and conveniently at the site of use has become a problem that hinders the large-scale application of ozone. Boron-doped diamond film electrode (BDD electrode) has obvious advantages as the anode of the membrane electrode assembly of the ozone generator. It has stable chemical properties, strong corrosion resistance, excellent conductivity, wide potential window and other characteristics. Therefore, boron-doped diamond film electrode has a very broad application prospect in the field of ozone generators. However, the adsorption performance of boron-doped diamond film electrode is low. The poor adsorption performance affects its adsorption capacity for oxygen-containing substances in the process of preparing ozone, and the ozone production decreases accordingly. Therefore, if you want to realize the widespread application of boron-doped diamond film electrode, you must improve the adsorption performance of boron-doped diamond film electrode, thereby increasing the ozone production of ozone generator. Summary of the invention
[0003] In order to overcome the shortcomings and deficiencies in the prior art, the purpose of the present invention is to provide a CNT-BDD electrode with high adsorption performance, which has the advantages of both boron-doped diamond film electrode and carbon nanotubes, and has excellent chemical stability, corrosion resistance, conductivity, a wide potential window and good adsorption performance.
[0004] Another object of the present invention is to provide a method for preparing a CNT-BDD electrode. The boron-doped diamond film layer and the carbon nanotube layer in the CNT-BDD electrode prepared by the preparation method have a nested structure, which has the advantages of both the boron-doped diamond film electrode and the carbon nanotube.
[0005] The object of the present invention is achieved through the following technical solution: a CNT-BDD electrode with high adsorption performance, the CNT-BDD electrode comprising a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0006] Specifically, the CNT-BDD electrode is a carbon nanotube-boron-doped diamond composite electrode. The present invention makes the CNT-BDD electrode by compounding carbon nanotubes with good adsorption and activity with boron-doped diamond, so that the CNT-BDD electrode has the advantages of both the boron-doped diamond film electrode and the carbon nanotube, and has excellent chemical stability, corrosion resistance, conductivity and a wide potential window, while effectively solving the problem of low adsorption performance of the boron-doped diamond electrode. Compared with the boron-doped diamond electrode, the ozone production of the membrane electrode assembly made of the CNT-BDD electrode of the present invention is significantly improved.
[0007] Another object of the present invention is achieved by the following technical solution: A method for preparing a CNT-BDD electrode, comprising the following steps:
[0008] (1) Pretreatment of the titanium substrate;
[0009] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0010] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0011] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 4-6 times, and the carbon nanotube layer is deposited 3-5 times.
[0012] Preferably, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times. The CNT-BDD electrode prepared by the above method has a high nucleation rate of the boron-doped diamond film. A boron-doped diamond film layer is first deposited on the titanium substrate and then the carbon nanotube layer is deposited. This is repeated several times, and the outermost layer that contacts the water body is the boron-doped diamond film layer, so that the boron-doped diamond film layer and the carbon nanotube layer are nested in layers, and the combination is tighter; the CNT-BDD electrode prepared by the above method has the advantages of both the boron-doped diamond film electrode and the carbon nanotube, and has excellent chemical stability, corrosion resistance, conductivity and a wide potential window. At the same time, it effectively solves the problem of low adsorption performance of the boron-doped diamond electrode. Compared with the pure boron-doped diamond electrode, the ozone production of the membrane electrode assembly made of the CNT-BDD electrode prepared by the preparation method has been significantly improved.
[0013] Furthermore, in the step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then placing the titanium substrate in an acetone mixture containing diamond powder for ultrasonic treatment, and then cleaning it with anhydrous ethanol.
[0014] Using diamond abrasive paste to polish the surface of the titanium substrate can not only make the surface of the titanium substrate have uniform scratches, but also remove the oxide layer on the surface of the titanium substrate. In addition, after polishing, some diamond particles in the diamond abrasive paste will adhere to the surface of the titanium substrate, which can improve the nucleation rate of the subsequent boron-doped diamond film; placing the polished titanium substrate in an acetone mixture containing diamond powder for ultrasonic treatment can not only remove oil stains on the surface of the titanium substrate, but also increase the number of diamond particles attached to the scratches on the surface of the titanium substrate. Finally, anhydrous ethanol is used to remove residual acetone and other dirt.
[0015] Furthermore, the ultrasonication time in step (1) is 10-15 min.
[0016] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0017] Specifically, the hydrogen, methane and hydrogen with trimethyl borate are mixed evenly before entering the reaction chamber. The above preparation process is simple, safe, controllable, and has a high boron doping success rate. The prepared boron-doped diamond film has high quality, complete crystal form, dense structure, and uniform coverage.
[0018] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0019] The trimethyl borate is used as a liquid boron source for preparing a boron-doped diamond film layer. Compared with a gaseous boron source, it is non-toxic and volatile, has high safety, and can be easily carried into the reaction chamber by hydrogen to participate in the reaction.
[0020] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0021] The power of the tantalum wire after high-temperature carbonization is stable, and the substrate temperature field in the reaction chamber fluctuates slightly during the boron-doped diamond film deposition reaction, which is beneficial to improving the quality of the boron-doped diamond film and can prevent the tantalum wire from forming tantalum vapor during the deposition process to contaminate the boron-doped diamond film.
[0022] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0023] Specifically, the anionic-cationic mixed surfactant solution is a solution in which anionic surfactant and cationic surfactant are dissolved. The above preparation process is simple, safe, controllable, and has high deposition efficiency. The thickness of the carbon nanotube layer is easy to control. The carbon nanotube layer deposited by the above steps is tightly combined with the boron-doped diamond film layer, and can significantly improve the adsorption performance of the CNT-BDD electrode, thereby increasing the ozone production of the membrane electrode assembly.
[0024] Furthermore, the electroplating time of step (3) is 2.5-4.5 min, and the electroplating voltage is 28-34 V.
[0025] The present invention controls the thickness and compactness of the carbon nanotube layer by strictly controlling the electrodeposition time. If the deposition time is too short, the thickness of the carbon nanotube layer will be insufficient, and the adsorption performance of the CNT-BDD electrode will not be significantly improved. If the deposition time is too long, the thickness of the carbon nanotube layer will be too thick, and the carbon nanotube layer will completely cover the boron-doped diamond film layer, affecting the contact between the boron-doped diamond film layer and the water body, resulting in a decrease in ozone production.
[0026] Furthermore, the heating temperature of the filament in step (2) is 1800-2000° C., and the deposition time each time is 20-30 minutes.
[0027] The present invention strictly controls the heating temperature of the filament and the deposition time of the boron-doped diamond film, thereby controlling the quality and thickness of the boron-doped diamond film. If the heating temperature is too high or too low, it is not conducive to the deposition of the boron-doped diamond film. If the heating temperature is too high, the carbon nanotubes deposited in step (3) will be oxidized and decomposed when step (2) is repeated. If the deposition time is too long, the thickness of the single-layer boron-doped diamond film will be too thick, and the single-layer boron-doped diamond film will completely cover the carbon nanotube layer, resulting in that the adsorption performance of the CNT-BDD electrode is not significantly improved, and it is not conducive to the combination between the boron-doped diamond film and the carbon nanotube layer. If the deposition time is too short, the single-layer boron-doped diamond film will be deposited unevenly, which is not conducive to the generation of ozone.
[0028] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 2.5-4g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0029] The suspension performance of carbon nanotubes in a solution containing both cationic surfactants and anionic surfactants is better than that in a solution containing any single surfactant. The ultrasound in step (3) provides energy for breaking up carbon nanotube aggregates, which plays an important role in the suspension and dispersion of carbon nanotube particles in the anionic-cationic mixed surfactant solution.
[0030] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.02-0.04 mol / L, and the concentration of the anionic surfactant is 0.03-0.045 mol / L.
[0031] Specifically, the cationic surfactant may be, but is not limited to, sodium octanoate, and the anionic surfactant may be, but is not limited to, dodecyltrimethylammonium bromide.
[0032] The suspension performance of carbon nanotubes in a solution containing both cationic surfactants and anionic surfactants is better than that of any single surfactant, and the suspension performance of carbon nanotubes in the solution is further improved by limiting the concentrations of the cationic surfactant and the anionic surfactant.
[0033] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 10-25 nm.
[0034] The van der Waals force between single-walled carbon nanotubes with relatively large diameters is relatively small, which can effectively promote the suspension and dispersion of single-walled carbon nanotubes in anionic-cationic mixed surfactants and is beneficial to the deposition of carbon nanotubes.
[0035] The beneficial effect of the present invention is that: the present invention composites carbon nanotubes with good adsorption and activity with boron-doped diamond to form a CNT-BDD electrode, so that the CNT-BDD electrode has the advantages of both the boron-doped diamond film electrode and the carbon nanotube, has excellent chemical stability, corrosion resistance, conductivity, a wide potential window and good adsorption performance, and effectively solves the problem of low adsorption performance of the boron-doped diamond electrode. Compared with the boron-doped diamond electrode, the ozone production of the membrane electrode assembly made of the CNT-BDD electrode of the present invention is significantly improved.
[0036] The present invention deposits a boron-doped diamond film layer on a titanium substrate first and then deposits a carbon nanotube layer, and repeats this process several times, stacking the layers one by one, and finally forming a boron-doped diamond film layer in contact with water, so that the boron-doped diamond film layer and the carbon nanotube layer are in a nested structure with tighter combination. The CNT-BDD electrode prepared by the preparation method of the present invention has a high nucleation rate of the boron-doped diamond film, has the advantages of both the boron-doped diamond film electrode and the carbon nanotube, has excellent chemical stability, corrosion resistance, electrical conductivity, a wide potential window and good adsorption performance, and effectively solves the problem of low adsorption performance of the boron-doped diamond electrode. Compared with the boron-doped diamond electrode, the ozone production of the membrane electrode assembly prepared by the CNT-BDD electrode of the present invention is significantly improved. DETAILED DESCRIPTION
[0037] In order to facilitate understanding by those skilled in the art, the present invention is further described below, and the contents mentioned in the implementation modes are not limitations of the present invention.
[0038] Example 1
[0039] In this embodiment, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode includes a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0040] A method for preparing a CNT-BDD electrode comprises the following steps:
[0041] (1) Pretreatment of the titanium substrate;
[0042] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0043] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0044] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 4 times, and the carbon nanotube layer is deposited 3 times.
[0045] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0046] Furthermore, the ultrasonication time in step (1) is 10 minutes.
[0047] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0048] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0049] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0050] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0051] Furthermore, the electroplating time of step (3) is 2.5 min, and the electroplating voltage is 28 V.
[0052] Furthermore, the heating temperature of the filament in step (2) is 1800° C., and the deposition time each time is 20 minutes.
[0053] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 2.5g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0054] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.02 mol / L, and the concentration of the anionic surfactant is 0.03 mol / L.
[0055] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0056] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 10 nm.
[0057] Example 2
[0058] In this embodiment, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode includes a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0059] A method for preparing a CNT-BDD electrode comprises the following steps:
[0060] (1) Pretreatment of the titanium substrate;
[0061] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0062] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0063] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited four times, and the carbon nanotube layer is deposited three times.
[0064] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0065] Furthermore, the ultrasonication time in step (1) is 11 minutes.
[0066] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0067] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0068] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0069] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0070] Furthermore, the electroplating time of step (3) is 3 minutes, and the electroplating voltage is 29V.
[0071] Furthermore, the heating temperature of the filament in step (2) is 1850° C., and the deposition time each time is 22 minutes.
[0072] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 2.8g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0073] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.025 mol / L, and the concentration of the anionic surfactant is 0.033 mol / L.
[0074] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0075] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 14 nm.
[0076] Example 3
[0077] In this embodiment, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode includes a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0078] A method for preparing a CNT-BDD electrode comprises the following steps:
[0079] (1) Pretreatment of the titanium substrate;
[0080] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0081] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0082] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times.
[0083] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0084] Furthermore, the ultrasonication time in step (1) is 13 minutes.
[0085] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0086] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0087] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0088] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0089] Furthermore, the electroplating time of step (3) is 3.5 min, and the electroplating voltage is 31 V.
[0090] Furthermore, the heating temperature of the filament in step (2) is 1900° C., and the deposition time each time is 25 minutes.
[0091] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 3.2g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0092] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.03 mol / L, and the concentration of the anionic surfactant is 0.038 mol / L.
[0093] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0094] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 18 nm.
[0095] Example 4
[0096] In this embodiment, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode includes a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0097] A method for preparing a CNT-BDD electrode comprises the following steps:
[0098] (1) Pretreatment of the titanium substrate;
[0099] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0100] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0101] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 6 times, and the carbon nanotube layer is deposited 5 times.
[0102] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0103] Furthermore, the ultrasonication time in step (1) is 14 minutes.
[0104] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0105] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0106] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0107] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0108] Furthermore, the electroplating time of step (3) is 4 minutes, and the electroplating voltage is 32V.
[0109] Furthermore, the heating temperature of the filament in step (2) is 1950° C., and the deposition time each time is 28 minutes.
[0110] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 3.6g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0111] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.035 mol / L, and the concentration of the anionic surfactant is 0.042 mol / L.
[0112] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0113] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 22 nm.
[0114] Example 5
[0115] In this embodiment, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode includes a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0116] A method for preparing a CNT-BDD electrode comprises the following steps:
[0117] (1) Pretreatment of the titanium substrate;
[0118] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0119] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0120] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 6 times, and the carbon nanotube layer is deposited 5 times.
[0121] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0122] Furthermore, the ultrasonication time in step (1) is 15 minutes.
[0123] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0124] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0125] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0126] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0127] Furthermore, the electroplating time of step (3) is 4.5 min, and the electroplating voltage is 34 V.
[0128] Furthermore, the heating temperature of the filament in step (2) is 2000° C., and the deposition time each time is 30 minutes.
[0129] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 4g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0130] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.04 mol / L, and the concentration of the anionic surfactant is 0.045 mol / L.
[0131] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0132] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 25 nm.
[0133] Comparative Example 1
[0134] In this comparative example, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode comprises a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0135] A method for preparing a CNT-BDD electrode comprises the following steps:
[0136] (1) depositing a boron-doped diamond film layer on the surface of a titanium substrate;
[0137] (2) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0138] (3) Repeating the above steps (1) and (2), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times.
[0139] Furthermore, the specific steps of step (1) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0140] Specifically, the specific steps of passing the hydrogen gas containing trimethyl borate into the reaction chamber in step (1) are as follows: the hydrogen gas in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen gas discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0141] Furthermore, the filament in step (1) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0142] Furthermore, the specific steps of step (2) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (1) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0143] Furthermore, the electroplating time of step (2) is 3.5 min, and the electroplating voltage is 31 V.
[0144] Furthermore, the heating temperature of the filament in step (1) is 1900° C., and the deposition time each time is 25 minutes.
[0145] Furthermore, the specific preparation steps of the mixed solution A in step (2) are: prepare an anionic-cationic mixed surfactant solution, add 3.2g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0146] Furthermore, the anionic-cationic mixed surfactant solution in step (2) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.03 mol / L, and the concentration of the anionic surfactant is 0.038 mol / L.
[0147] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0148] Furthermore, the ultrasonic time in step (2) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 18 nm.
[0149] The rest of the contents of this comparative example are the same as those of Example 3 and will not be repeated here.
[0150] Comparative Example 2
[0151] In this comparative example, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode comprises a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0152] A method for preparing a CNT-BDD electrode comprises the following steps:
[0153] (1) Pretreatment of the titanium substrate;
[0154] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0155] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0156] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited twice, and the carbon nanotube layer is deposited once.
[0157] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then placing the titanium substrate in an acetone mixture containing diamond powder for ultrasonic treatment, and then cleaning with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0158] Furthermore, the ultrasonication time in step (1) is 13 minutes.
[0159] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0160] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0161] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0162] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0163] Furthermore, the electroplating time of step (3) is 3.5 min, and the electroplating voltage is 31 V.
[0164] Furthermore, the heating temperature of the filament in step (2) is 1900° C., and the deposition time each time is 25 minutes.
[0165] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 3.2g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0166] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.03 mol / L, and the concentration of the anionic surfactant is 0.038 mol / L.
[0167] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0168] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 18 nm.
[0169] The rest of the contents of this comparative example are the same as those of Example 3 and will not be repeated here.
[0170] Comparative Example 3
[0171] In this comparative example, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode comprises a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0172] A method for preparing a CNT-BDD electrode comprises the following steps:
[0173] (1) Pretreatment of the titanium substrate;
[0174] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0175] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0176] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times.
[0177] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0178] Furthermore, the ultrasonication time in step (1) is 13 minutes.
[0179] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0180] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0181] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0182] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0183] Furthermore, the electroplating time of step (3) is 7 minutes, and the electroplating voltage is 31V.
[0184] Furthermore, the heating temperature of the filament in step (2) is 2200° C., and the deposition time each time is 40 minutes.
[0185] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 3.2g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0186] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.03 mol / L, and the concentration of the anionic surfactant is 0.038 mol / L.
[0187] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0188] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 18 nm.
[0189] The rest of the contents of this comparative example are the same as those of Example 3 and will not be repeated here.
[0190] Comparative Example 4
[0191] In this comparative example, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode comprises a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0192] A method for preparing a CNT-BDD electrode comprises the following steps:
[0193] (1) Pretreatment of the titanium substrate;
[0194] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0195] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0196] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times.
[0197] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0198] Furthermore, the ultrasonication time in step (1) is 13 minutes.
[0199] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0200] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0201] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0202] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in a cationic surfactant solution to prepare a mixed solution A, placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0203] Furthermore, the electroplating time of step (3) is 3.5 min, and the electroplating voltage is 31 V.
[0204] Furthermore, the heating temperature of the filament in step (2) is 1900° C., and the deposition time each time is 25 minutes.
[0205] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare a cationic surfactant solution, add 3.2g of carbon nanotube particles to every 1L of cationic surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles uniformly dispersed in the cationic surfactant solution to obtain mixed solution A.
[0206] Furthermore, the cationic surfactant solution in step (3) is prepared by the following steps: dissolving a cationic surfactant in water, wherein the concentration of the cationic surfactant is 0.06 mol / L.
[0207] Specifically, the cationic surfactant is sodium octanoate.
[0208] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 18 nm.
[0209] The rest of the contents of this comparative example are the same as those of Example 3 and will not be repeated here.
[0210] Comparative Example 5
[0211] In this comparative example, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode comprises a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0212] A method for preparing a CNT-BDD electrode comprises the following steps:
[0213] (1) Pretreatment of the titanium substrate;
[0214] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0215] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0216] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times.
[0217] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0218] Furthermore, the ultrasonication time in step (1) is 13 minutes.
[0219] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0220] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0221] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0222] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: placing carbon nanotube particles in an anionic-cationic mixed surfactant solution and shaking to obtain a mixed solution A, placing the electrode after step (2) in the mixed solution A and serving as an anode, using a stainless steel plate as a cathode, and performing electrodeposition to deposit carbon nanotubes on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0223] Furthermore, the electroplating time of step (3) is 3.5 min, and the electroplating voltage is 31 V.
[0224] Furthermore, the heating temperature of the filament in step (2) is 1900° C., and the deposition time each time is 25 minutes.
[0225] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 3.2g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution, and shake the mixture after adding to obtain the mixed solution A.
[0226] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.03 mol / L, and the concentration of the anionic surfactant is 0.038 mol / L.
[0227] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0228] Furthermore, the carbon nanotube is a single-walled carbon nanotube, and the diameter of the carbon nanotube is 18 nm.
[0229] The rest of the contents of this comparative example are the same as those of Example 3 and will not be repeated here.
[0230] Comparative Example 6
[0231] In this comparative example, a CNT-BDD electrode with high adsorption performance is provided. The CNT-BDD electrode comprises a titanium substrate, a boron-doped diamond layer deposited on the titanium substrate, and a carbon nanotube layer.
[0232] A method for preparing a CNT-BDD electrode comprises the following steps:
[0233] (1) Pretreatment of the titanium substrate;
[0234] (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate;
[0235] (3) depositing a carbon nanotube layer on the boron-doped diamond layer;
[0236] (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 5 times, and the carbon nanotube layer is deposited 4 times.
[0237] Furthermore, in step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then ultrasonicating the titanium substrate in an acetone mixture containing diamond powder, and then cleaning it with anhydrous ethanol. Specifically, the particle size of the diamond powder is 0.3 μm.
[0238] Furthermore, the ultrasonication time in step (1) is 13 minutes.
[0239] Furthermore, the specific steps of step (2) are: using a chemical vapor deposition furnace to deposit a boron-doped diamond film layer on the surface of a titanium substrate: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and respectively passing hydrogen, methane and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition.
[0240] Specifically, the flow rate of methane is 4.5 ml / min, the flow rate of hydrogen is 220 ml / min, the flow rate of trimethyl borate in the hydrogen with trimethyl borate is 8 ml / min, and the flow rate of hydrogen in the hydrogen with trimethyl borate is 11 ml / min. More specifically, the specific steps of passing the hydrogen with trimethyl borate into the reaction chamber in step (2) are as follows: the hydrogen in the gas channel is passed into a gas washing bottle containing trimethyl borate, and the hydrogen discharged from the gas washing bottle brings the volatilized trimethyl borate into the reaction chamber.
[0241] Furthermore, the filament in step (2) is a tantalum wire, and the tantalum wire is carbonized at high temperature until the resistance of the tantalum wire is stable before depositing the boron-doped diamond film layer.
[0242] Furthermore, the specific steps of step (3) are as follows: depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed.
[0243] Furthermore, the electroplating time of step (3) is 3.5 min, and the electroplating voltage is 31 V.
[0244] Furthermore, the heating temperature of the filament in step (2) is 1900° C., and the deposition time each time is 25 minutes.
[0245] Furthermore, the specific preparation steps of the mixed solution A in step (3) are: prepare an anionic-cationic mixed surfactant solution, add 3.2g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and perform ultrasonic treatment to make the carbon nanotube particles evenly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
[0246] Furthermore, the anionic-cationic mixed surfactant solution in step (3) is prepared by the following steps: a cationic surfactant and an anionic surfactant are dissolved in water, wherein the concentration of the cationic surfactant is 0.03 mol / L, and the concentration of the anionic surfactant is 0.038 mol / L.
[0247] Specifically, the cationic surfactant is sodium octanoate, and the anionic surfactant is dodecyltrimethylammonium bromide.
[0248] Furthermore, the ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 2 nm.
[0249] The rest of the contents of this comparative example are the same as those of Example 3 and will not be repeated here.
[0250] The CNT-BDD electrodes prepared in Examples 1-5 and Comparative Examples 1-6 of the present invention were used as anodes, stainless steel electrodes were used as cathodes, and perfluorosulfonic acid proton exchange membranes (Nafion membranes) were used as ion exchange membranes to form membrane electrode assemblies. The membrane electrode assemblies were used in ozone generators to prepare ozone. Pure water was used as a raw material. Ozone formation tests were performed under the conditions of a voltage of 10 V and a current of 1.5 A. The present invention also provides a group of comparative examples 7: BDD electrodes of Jingan Bio were used as anodes, stainless steel electrodes were used as cathodes, and perfluorosulfonic acid proton exchange membranes (Nafion membranes) were used as ion exchange membranes to form membrane electrode assemblies. The membrane electrode assemblies were used in ozone generators to prepare ozone. Pure water was used as a raw material. Ozone formation tests were performed under the conditions of a voltage of 10 V and a current of 1.5 A. The results are shown in the following table:
[0251]
[0252]
[0253] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a CNT-BDD electrode, characterized in that: The steps include: (1) Pretreatment of the titanium substrate; (2) depositing a boron-doped diamond film layer on the surface of the pretreated titanium substrate using a chemical vapor deposition furnace: placing the pretreated titanium substrate in a reaction chamber of the chemical vapor deposition furnace, then heating the filament in the reaction chamber, and introducing hydrogen, methane, and hydrogen with trimethyl borate into the reaction chamber through different gas channels for thermal deposition; (3) depositing a carbon nanotube layer on the boron-doped diamond layer by electrodeposition: dispersing carbon nanotube particles in an anionic-cationic mixed surfactant solution to prepare a mixed solution A; placing the electrode after step (2) in the mixed solution A as an anode, and using a stainless steel plate as a cathode to perform electrodeposition so that the carbon nanotubes are deposited on the outside of the boron-doped diamond film layer, and taking out and drying after the deposition is completed; (4) Repeating the above steps (2) and (3), wherein the outermost layer is a boron-doped diamond film layer, the boron-doped diamond film layer is deposited 4-6 times, and the carbon nanotube layer is deposited 3-5 times.
2. The method for preparing a CNT-BDD electrode according to claim 1, characterized in that: In the step (1), the specific steps of pretreatment include: grinding the surface of the titanium substrate with diamond grinding paste, then placing the titanium substrate in an acetone mixture containing diamond powder for ultrasonic treatment, and then cleaning it with anhydrous ethanol.
3. The method for preparing a CNT-BDD electrode according to claim 1, characterized in that: The electroplating time of step (3) is 2.5-4.5 min, and the electroplating voltage is 28-34 V.
4. The method for preparing a CNT-BDD electrode according to claim 1, characterized in that: The heating temperature of the filament in the step (2) is 1800-2000° C., and the deposition time each time is 20-30 minutes.
5. The method for preparing a CNT-BDD electrode according to claim 1, characterized in that: The specific preparation steps of the mixed solution A in step (3) are: preparing an anionic-cationic mixed surfactant solution, adding 2.5-4g of carbon nanotube particles to every 1L of the anionic-cationic mixed surfactant solution and performing ultrasonic treatment to make the carbon nanotube particles uniformly dispersed in the anionic-cationic mixed surfactant solution to obtain a mixed solution A.
6. The method for preparing a CNT-BDD electrode according to claim 1, characterized in that: The ultrasonic time in step (3) is 20 minutes, the carbon nanotubes are single-walled carbon nanotubes, and the diameter of the carbon nanotubes is 10-25 nm.